Analysis of Mudharabah and Musyarakah Financing at Panin Dubai Syariah Bank - Supriyadi, Djoko; Hasan, Asyari (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this study was to analyze the relationship between the inflation rate, the BI 7 Day Reverse Repo Rate (BI-7 Day RR), and the money supply on Mudharabah and Musyarakah financing at Panin Dubai Syariah Bank. This type of research is quantitative research using secondary data. The data analysis technique used in this research is descriptive statistics, classical assumption test, and hypothesis testing with the OLS method. Inflation rate, BI 7 Day Reverse Repo Rate (BI-7 Day RR), and money supply act as independent variables while Mudharabah financing and Musyarakah financing act as dependent variables. Based on the test results, the money supply factor has a significant effect on Musyarakah's financing. The implication of this research is that Bank Panin Dubai Syariah should focus on the circulation of the money supply in the community which shows an escalation of people's purchasing power so that they are able to implement policies that make Musyarakah financing more needed by the community.